The Creative Ability of Student through Contextual Based Social Science in Class IV Primary School - Amaliyah, Elis Nur Elisah; Sapriya, Sapriya; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Contextual learning presents new concepts in real life experiences and situations where students can find meaningful relationships between abstract ideas and practical applications. This study aims to determine students' creative thinking skills through contextualbased learning in fourth grade students of elementary schools. The design of this study uses the basic pattern of Pre test and Post test one Control Group with quasi-experimental type. The sample of this study was 40 students. The data collected is the ability of students 'creative thinking using Annova SPSS 23. The results of the hypothesis test of this study prove that contextual ability-based learning abilities of students' creative thinking are better than conventional learning. This is proven by the average score of students' creative thinking abilities in the experimental class being higher than conventional classes